Executive Committee Minutes 2005-12-08 - Academic Senate:::::::::
Priority Registration Policy, New Electives in CCJ, New Courses in WGS, Sociology Curriculum Course Changes, Allocation of Unused Senate units. Policies on Consultation from S&F, Academic Calendar